Kazimierza Twardowskiego koncepcja wytworów czynności - Brykczyński, Piotr (Filozofia Nauki, 2005)
The aim of the paper is to provide a presentation and evaluation of Kazimierz Twardowski's conception, the subject matter and contents of which is delimited, roughly by (Twardowski 1965a). Since there is no separate problematization of the notion of action in Twardowski, it is maintained that the conception in question should be characterized rather as a conception of "products of actions" (hence the term "Twardowski's conception of products of actions") and not as a conception of "actions and products" - contrary to what is suggested by the title of the above mentioned Twardowski's paper. Twardowski's conception of products of actions includes a conception which has the general notion of products of actions as its central notion, and which belongs to philosophy of action. This conception has been called "Twardowski's general conception of products of actions". It is supplemented by some conceptions which can be characterised, roughly, as based on it (I.3.). Among the theses that belong to the general conception are the theses that make together what has been called in the paper "the conception of nonpermanent products as events" (II.7.). There is also a thesis to the effect that each action has but one product (II.1.), and a thesis which eliminates the material of actions from their products (II.11.). As for the conceptions which are based on Twardowski's general conception of products of actions, all but one belong to the logic of language and semiotics. They include Twardowski's conception of meaning and, within its confines, his conception of proposition as the product of judgement. The presentation and evaluation of Twardowski's conception of products of actions often requires preparatory considerations of a purely ontological, epistemological and/or methodological character. A separate section (II.8.) is devoted entirely to some ontological problems of complexity with the question of "empty" parts as the question in focus. Twardowski's conception of products of actions has to be seen as making a contribution to the research on the ontological foundations of philosophy of action and philosophy of mind. If the objections that have been raised against it are correct, the importance of its contribution to this research may be questioned (IV.1.). Such is f.e. the import of the objections raised against Twardowski's conception of meaning: while this conception seems at first sight to substantially widen our perspectives in respect of the ontic status of meanings, the corrections proposed as a result of its critical appraisal reduce all that can have a claim to originality to a variant of the thesis to the effect that meanings are defective in respect of ontic autonomy (III.2.6.). The results presented in the paper have some bearing on the question of Twardowski's attitude towards psychologism, as well as his contribution to the battle against it: on the one hand there seems to be no reason to question Twardowski's position as a consistent antipsy